재조합 HCCS-1 아데노바이러스를 이용한 구강암 세포주의 세포사멸 유발 - 김창현(Chang-Hyen Kim); 이동주(Dong-Ju Lee); 이일규(ll-Kyu Lee); 김명진(Myung-Jin Kim); 김진우(Jin-Woo Kim); 표성운(Sung-Woon Pyo) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2005)
Despite advances in surgery, radiotherapy, and chemotherapy, the survival of patients with oral squamous cell carcinoma has not significantly improved over the past several decades. Gene therapy is currently under investigation and shows us new possibility of cancer curing method. This experiment was undergone to find out the cell growth inhibition effect and evidence of apoptosis by HCCS-1(human cervical cancer suppressor-1), one of the candidates of tumor suppressor gene, transducted to human oral cancer cell line. To determine the efficiency of the adenovirus as a gene delivery vector cell line was transducted with LacZ gene and analysed with X-gal staining. Northern blot was performed to confirm the transfection with HSCC-1 gene and cell viability was assessed by cell cytotoxicity assay using cell count kit(CCK). To show the evidence of apoptosis, DNA fragmentation assay and flow cytometry(FACS) were performed. We had successfully construct the recombinant HSCC-1 adenovirus(Ad5CMV-HCCS-1), and importation efficiency was 20% at 2 MOI(multiplicity of infection), 80% at 20 MOI. Northern blot analysis showed that a single 0.6kb mRNA transcript was expressed in Ad5CMV-HCCS-1 transducted cell lines. As a result of CCK, when comparing to control subjects, transducted group showed 50% growth inhibition. In DNA fragmentation assay, according to increasing of MOI, DNA volume was diminished. In FACS analysis, DNA distribution showed fragmentation. This results imply that HCCS-1gene has growth inhibition effect in human oral cancer cell lines through apoptosis induction. KCI Citation Count: 0